Enhancing MSME Competitiveness Through Creative Branding and Live Streaming: A Case Study of LSPR’s Community Service Program - Latifa Ramonita; Elke Alexandrina; J. A. Wempi; Yesi Pandu Pratama Wibowo DC; Febrina Ramadyanti (Universitas Pendidikan Ganesha, 2025)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in understanding branding concepts and utilizing live streaming as a digital marketing strategy. Limited digital literacy and technical readiness reduce the competitiveness of MSMEs in the digital marketplace. This community service project aimed to evaluate the effectiveness of creative branding training and live streaming strategies in enhancing MSMEs’ knowledge and skills in digital marketing, using a descriptive qualitative approach through a participatory case study design. The subjects included 50 MSME actors. Data were collected through participatory observation, semi-structured interviews, and pre- and post-training evaluation questionnaires. The questionnaires were developed based on a competency evaluation framework encompassing branding knowledge, understanding of digital marketing strategies, social media skills, technical and non-technical readiness for live streaming, and self-confidence levels. Data were analyzed using thematic analysis for qualitative data and descriptive quantitative analysis for survey data. The results indicate that the training significantly improved participants’ understanding of branding, ability to design marketing strategies based on the 7P framework, and practical live streaming skills. Live streaming simulations, in particular, enhanced participants’ confidence in engaging with digital audiences. The study concludes that creative branding and live streaming training effectively increase MSMEs’ readiness to independently implement digital marketing strategies.